2016
DOI: 10.1371/journal.pone.0160909
|View full text |Cite
|
Sign up to set email alerts
|

Low Night Temperature Affects the Phloem Ultrastructure of Lateral Branches and Raffinose Family Oligosaccharide (RFO) Accumulation in RFO-Transporting Plant Melon (Cucumismelo L.) during Fruit Expansion

Abstract: Due to the importance and complexity of photo assimilate transport in raffinose family oligosaccharide (RFO)-transporting plants such as melon, it is important to study the features of the transport structure (phloem) particularly of the lateral branches connecting the source leaves and the sink fruits, and its responses to environmental challenges. Currently, it is unclear to what extents the cold environmental temperature stress would alter the phloem ultrastructure and RFO accumulation in RFO-transporting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…As expected, one TPS gene, here, was up-regulated by both dehydration and salt. Raffinose family oligosaccharides (RFO) including raffinose, stachyose, and verbascose significantly accumulate in leaves of plants experiencing environmental stress such as cold, drought or high salinity 53 54 55 56 . GolS (galactinol synthase) and StS (Stachyose synthase) are two important enzymes in RFO pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, one TPS gene, here, was up-regulated by both dehydration and salt. Raffinose family oligosaccharides (RFO) including raffinose, stachyose, and verbascose significantly accumulate in leaves of plants experiencing environmental stress such as cold, drought or high salinity 53 54 55 56 . GolS (galactinol synthase) and StS (Stachyose synthase) are two important enzymes in RFO pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, two GolS members and two StS members were positively responded to dehydration or/and salt. In Arabidopsis, over-expressing GolS lead to accumulating high levels of galactinol and raffinose and more tolerant to drought and salinity stress 54 56 . However, upon StS gene, no data, to date, is available, which remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The contents of sugar components and starch in lettuce were measured with proper modification [14,15].…”
Section: Measurement Of Sugar Components and Starchmentioning
confidence: 99%
“…Specifically, chilling stress reduces leaf expansion rates and leaf area in sorghum (Sorghum bicolor), maize, and sunflower (Helianthus annuus; Tardieu et al, 1999). LNT stress can also reduce leaf growth, the concentration of photosynthetic pigments and shoot and root dry matter accumulation in tomato (Latef and He, 2011), melon (Hao et al, 2016), and peanut (Song et al, 2020). We demonstrated that even a short-term (11 HoL) overnight chilling stress significantly increased soluble sugar, starch, and total nonstructural carbohydrate concentrations in leaves (Figures 2A-C).…”
Section: Discussion Lnt Stress-induced Feedback Inhibition Of Photosymentioning
confidence: 99%